From the Farm to the Table: What All Americans Need to Know about Agriculture - GARY HOLTHAUS (University Press of Kentucky, 2014)
For the past three years, I have been talking with, and learning from, folks who understand, as best any of us can, how agriculture works. In the process, I've visited with almost forty farm families in southeast Minnesota, northern Iowa, and western Wisconsin. Some of those visits lasted half a day or more and included a firsthand look at the farm. In some cases I've been back several times. Tve also spoken with university faculty in our land-grant institutions, talked with county extension educators, attended too many public meetings and farm field days to count, and shopped at local farmers' markets—all for a project initiated by a unique, citizen-led regional organization called the Experiment in Rural Cooperation, most often referred to by locals, and me too, as the Experiment. The Experiment is one of five regional partnerships created by the Minnesota state legislature and the University of Minnesota. For more than six years now, it has been putting funds into the hands of citizen leaders so they can use the resources of the state's land-grant university in projects that will lead to a sustainable society in this region. The people involved with the Experiment believe that there is a story to tell about farming in southeast Minnesota that is different from the story often told by the media. It is a story of success, at least some success, even on small farms, and of people who are having satisfactory lives, making a living by adapting their farm practices to their particular landscapes and nourishing them to bring health to the land and to the animals and humans who live on it. Together, these farmers, their university, and the Experiment itself represent an unusual ecosystem, a small habitat for hope amid a tide of issues that threatens to engulf us. What I have found is myriad stories about farming. Not only does every farmer have a story to tell, but each of the issues that both farmers and food consumers face has a story of its own. I did not set out to make an argument for one point of view or another about agriculture, but as I learned more, I had to develop a point of view, and it shows. Nevertheless, I have chosen to keep a story format, even for thorny issues like genetically modified organisms and the World Trade Organization. I have tried to let them, too, tell their own stories as best I can, while sorting through complexities, controversies, and complications. I hope that I have put together a comprehensible story without ducking any of the issues we need to sort out to create a sustainable culture.